Incidence and Sensitivity Pattern of Klebsiella Pneumoniae, Escherichia Coli and Pseudomonas Aeruginosa in a Tertiary Care Hospital - Rahul Radhakrishnan (Journal of Global Pharma Technology, 2019)
Objective: Antimicrobial resistance is a serious problem worldwide and differs from region to region. This study was carried out to determine the incidence and sensitivity pattern of gram negative bacteria mainly Klebsiella pneumoniae (K. pneumoniae), Escherichia coli (E. coli) and Pseudomonas aeruginosa (P. aeruginosa) in our region and discuss the general issues related to antimicrobial resistance. Methods: Retrospective study was carried out in 6 months. Samples of urine, blood, pus, CSF and miscellaneous samples (fluids, swabs, sputum and stool) were collected from indoor and outdoor patients for isolation and antimicrobial susceptibility of K. pneumoniae, E. coli and P. aeruginosa were carried out in the Department of Microbiology in a Tertiary care Hospital.Results: Out of the 800 samples analyzed 618 showed growth,where 427 samples were isolated and it constitutes E.coli (43.32%), K. pneumoniae (33.02%) and P. aeruginosa (23.65%). Both E.coli and K. pneumoniae showed highest sensitivity for doxycycline (73%; 65% resp.) and second highest for levofloxacin (68%; 62% resp.), whereas, P. aeruginosa showed highest 55% sensitivity for amikacin followed by 46% for levofloxacin. β-lactam antibiotics and aminoglycosides showed high mean resistance (K.pneumoniae-81%, E.coli-77%, P. aeruginosa-84.4%) and (K. pneumoniae-73%, E. coli-59%, P. aeruginosa-68%) respectively.Conclusion: The data indicates high resistance among the gram-negative bacteria for β-lactam and aminoglycoside antibiotics. This study concludes that a proper awareness about antibiotics is essential as well as proper measures is to be implemented to control irrational use of antibiotics in this region. Keywords: Antibiotics;  Antimicrobial sensitivity; Gram-negative bacteria; Resistance